Arthrodesis of the tarsometatarsal joint, using type II ESF with acrylic connecting bars in four dogs - Shani, J.; Yeshurun, Y.; Shahar, R. (Veterinary and Comparative Orthopaedics and Traumatology, 2006)
Hyperextension injury of the tarsometatarsal joint (TMTJ) is a debilitating injury and arthrodesis of this joint is often the only procedure that can result in full return to function. Most surgical procedures described for arthrodesis of the tarsometatarsal joint necessitate the use of external, splint or cast, to protect the implants used from fatigue failure. This report describes the successful use of type II external fixator that spans the tarsometatarsal joint in four dogs with hyperextension injury of the tarsometatarsal joint. This technique enables the patient to bear weight on the limb immediately after surgery until bony fusion is achieved, without the need for an additional protecting splint.
Keywords: Arthrodesis; tarsometatarsal joint; external fixator